The Standard Chromatografic Method For Determination of Paracetamol and Homatropin methyl bromide in Riabasam binary components - Khalaf F Alsamarrai; Ahmed Kareem Abbas (Tikrit Journal of Pure Science, 2023)
This study Includes innovative and validate RP-HPLC method for determination of drugs HMB and Para by using of  L7 column (25cm×4.6mm) and mobile phase content of Methanol: Buffer Phosphate: water with ratio 10:20:70 and pH 3.5 at 257 nm for HMB and 243 nm for Para. The calibration curves for determination HMB and Para were constructed at the concentrations (20–200) ppm for two drugs with recovery percentage for HMB (95.5–103.8)% and detection limit 0.00028 ppm and quantitate limit 0.000959 ppm and recovery percentage for Para (95.07–103.43)% and detection limit 0.000123ppm and quantitate limit 0.00041ppm. The method successfully applied to determination of two drugs in pure and in pharmaceutical forms.